Abandonment of Penguin Subcolonies in the Late Nineteenth Century on Inexpressible Island, Antarctica. Issue 12 (19th December 2020) - Xu, Q. B.; Gao, Y. S.; Yang, L. J.; Yang, W. Q.; Chu, Z. D.; Wang, Y. H.; Sun, L. G.; Xie, Z. Q.
Abstract: The impact of climate and weather on penguin ecology has attracted much research attention. To reconstruct the history of the penguin population, penguin carcasses on the surface and three ornithogenic sediment profiles were collected in a ditch area beneath abandoned penguin subcolonies on a high terrace to the northwest of the modern colony in Seaview Bay, on Inexpressible Island, East Antarctica. A rapid increase in penguin‐derived element contents in the sediment profiles at 1700 Common Era (CE) indicates an increase in the penguin population of research area at the end of the Little Ice Age. However, surficial carcasses, geochemical characteristics of the sediment profiles, and field evidence indicate the subsequent abandonment of these penguin subcolonies. A period of intensified streamflow activity resulting from meltwater is a possible explanation for the colony abandonment. The dating results of the carcasses and sediment profiles constrain this event to around the late nineteenth century. The meltwater streams can be attributed to the interaction between enhanced moist air mass transport to the coastline of Victoria Land, rising temperatures, and the sloping topography. Comparisons with other regional records suggest that this type of event is common across East Antarctica and has significant impacts on penguin ecology. Key Points: Reconstruction of penguin population changes in an area of abandoned subcolonies in Inexpressible Island (to the northwest of Seaview Bay), during the last three centuries Penguin population in the research area increased during the late Little Ice Age Penguin subcolonies in the research area were abandoned in the late nineteenth century